PENGARUH PROFITABILITAS, KOMITE AUDIT, DAN KEPEMILIKAN INSTITUSIONAL PADA TAX AVOIDANCE - Dalem Praja Dhita, I Dewa Gede; Agung Kresnandra, Anak Agung Ngurah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p09, 2024)
This study aims to determine how the influence of profitability, audit committee, and institutional ownership on tax avoidance. Profitability is measured by ROA, audit committee is measured by the number of audit committee members, and institutional ownership is measured by the proportion of outstanding shares owned by other institutions outside the company. This study uses a quantitative research method in the form of associative. This study used non-probability sampling method with purposive sampling technique and obtained a sample of 76. The results showed that profitability has no effect on tax avoidance, audit committee has no effect on tax avoidance, and institutional ownership has a significant negative effect on tax avoidance in companies. the food and beverage sub-sector on the IDX for the 2018-2021 period.